1607 Seeing White: Management of TIVA During Autologous Breast Reconstruction. (12th October 2021) - Vigneswaran, P; Clancy, R; Choo, S; Love-Jones, S; Jackson, P; Wilson, S
Abstract: Background: Free flap surgery has inherent risks, and the venous drainage of the Deep Inferior Epigastric Perforator (DIEP) flap is particularly vulnerable to congestion. In these cases, an algorithm for flap salvage should be followed and one of the final steps in this process is a cephalic vein transposition. Case Report: We describe two patients undergoing mastectomy and immediate bilateral DIEP breast reconstruction, where cephalic vein transposition was required. As part of the Enhanced Recovery After Surgery (ERAS) pathway, patients are anaesthetised with a continuous propofol infusion (Total Intravenous Anaesthesia; TIVA). When the cephalic vein was identified, the propofol infusion was visible within the vein, which would have interrupted TIVA if harvested. To maintain continuous TIVA infusion, the cannula was resited prior to harvest of the cephalic vein. The cephalic vein was anastomosed to the superficial inferior epigastric vein and resolution of the venous congestion was noted. Conclusions: These cases although rare highlight the importance of robust preoperative planning and communication between the team and preparation for all eventualities to ensure patient safety and successful outcomes. These cases highlight the potential effects vein harvesting or transposition may have on the safe and effective delivery of anaesthetic agents and other medication. We hope these cases prompt a discussion in the preoperative stage for alternate strategies for monitoring and intravenous access in response to diversions from the standard operating procedure.